Tổng hợp và xác định cấu trúc nano của polyeste dendritic - Khoa, Nguyễn Cửu; Kim Phụng, Lê Thị (Vietnam Journal of Chemistry, 2015)
Dendritic polymer based on polyester of trimethylol propane and dimethylol propanoic acid with the 3rd generations was synthesized. These dendrimers were modified by benzoyl chloride for determination of their nano sizes in solution of chloroform: acetone by TEM. The structures of synthesized dendrimers and modified dendrimers were determined by FT-IR, 1H-NMR and 13C-NMR.